1998
DOI: 10.1002/hep.510270427
|View full text |Cite
|
Sign up to set email alerts
|

Zonal and regional differences identified from precision mapping of vitamin a-storing lipid droplets of the hepatic stellate cells in pig liver: A novel concept of addressing the intralobular area of heterogeneity

Abstract: Knowledge of hepatic heterogeneity has been strikingly increased, while an accurate means for addressing intralobular positions is still lacking. We examined pig liver preparations of the gold impregnation method for vitamin A-storing lipid droplets in hepatic stellate cells. Droplet morphometry was performed under oil immersion, and the calculated volumes plotted on computerized maps. The heterogeneous results were assessed with five concentric zones and five radial regions; the latter were determined based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 39 publications
2
42
0
3
Order By: Relevance
“…It was previously reported that the liver lobule physiologically shows zonal heterogeneity in terms of vitamin A storage (Wake and Sato, 1993;Zou et al, 1998;Higashi and Senoo, 2003). In our present study, this heterogeneity of vitamin A storage disappeared during liver regeneration and did not return to normal by 14 days after PHx, at which time the liver volume generally does return to normal (Michalopoulos and DeFrances, 1997).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It was previously reported that the liver lobule physiologically shows zonal heterogeneity in terms of vitamin A storage (Wake and Sato, 1993;Zou et al, 1998;Higashi and Senoo, 2003). In our present study, this heterogeneity of vitamin A storage disappeared during liver regeneration and did not return to normal by 14 days after PHx, at which time the liver volume generally does return to normal (Michalopoulos and DeFrances, 1997).…”
Section: Discussionsupporting
confidence: 48%
“…Under physiological conditions, the HSCs store about 80% of the total vitamin A in the whole body as retinyl esters in lipid droplets in their cytoplasm, and they show heterogeneity in their vitamin A-storing capacity within the liver lobules (Wake and Sato, 1993;Zou et al, 1998). These cells also play a pivotal role in the regulation of vitamin A homeostasis (Senoo and Wake, 1985;Blomhoff et al, 1990;Senoo et al, 1990Senoo et al, , 1993aSenoo et al, , 1993bBlomhoff and Wake, 1991;Imai et al, 2000b).…”
mentioning
confidence: 99%
“…However, it does not explain lateral or portal-portal gradients between adjacent portal tracts as seen in animals and in humans. [8][9][10][11][12] The classic lobule is not the smallest functional unit but rather a composite of many smaller units, with the acinus as one conceptual candidate.…”
Section: The Functional Unit Of the Livermentioning
confidence: 99%
“…The second concept regards the distinction of these 2 zones, as a basis for explaining differences in the metabolic properties of hepatocytes across a lateral gradient as one moves from the portal tract to the midseptal region, in both humans and animals. [8][9][10][11][12] Matsumoto et al note that many pathological processes like fatty change, perivenular necrosis, and staining with glucose-6-phosphatase highlight the presence of a sickle zone. 12 However, if we do dare to extrapolate from amphibians and small mammals, an ''inflow front'' type of flow is not consistent with the variation in blood flow between adjacent sinusoids in the same lobule, as has been observed by direct visualization in living animals under a wet-mount microscope.…”
Section: Primary and Secondary Lobulementioning
confidence: 99%
“…Due to the liver's microvascular organisation and its metabolic functions, liver lobules are characterized by metabolic zonation [2,10]. For example, the cell zone closest to the PTs will receive blood that is rich in nutrients and oxygen, while the zone close to the CV receives blood that is poorer in nutrients and oxygen.…”
Section: Introductionmentioning
confidence: 99%